2020
DOI: 10.1136/bmjopen-2019-033354
|View full text |Cite
|
Sign up to set email alerts
|

Women’s experience of episiotomy: a qualitative study from China

Abstract: ObjectiveTo describe women’s experience of episiotomy in urban China.DesignThis is a semistructured, indepth interview with women after episiotomy. We analysed transcriptions using thematic analysis in Chinese. Emerging themes were debated in English to finalise interpretation.SettingTwo community health centres and four hospitals in Shanghai, China.ParticipantsPurposive sampling of 30 postpartum women who had experienced episiotomy; 25 were primiparous and 4 had deliveries by forceps. We interviewed health pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
2
26
0
4
Order By: Relevance
“…Episiotomies have diverse meanings to women depending on social context, professional background and personal perspective [33]. This means that they can have a wide range of physical and psychological consequences [34]. Women in this study did not perceive their episiotomy as a negative experience and felt it had been necessary to expedite a safe birth.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Episiotomies have diverse meanings to women depending on social context, professional background and personal perspective [33]. This means that they can have a wide range of physical and psychological consequences [34]. Women in this study did not perceive their episiotomy as a negative experience and felt it had been necessary to expedite a safe birth.…”
Section: Discussionmentioning
confidence: 74%
“…Women in this study appreciated the optimal communication from their midwives as a means of understanding their maternity care. One study reports that episiotomies have been performed without women's consent and understanding [34] and one woman in this study reported no memory of the episiotomy being performed. It is, however, unclear as to what effect analgesia, such as diamorphine, can have on memories of intrapartum events.…”
Section: Discussionmentioning
confidence: 76%
“…49 Instead of expectation, the effect of episiotomy was described in Chinese as a 'psychological shadow' of postpartum sexual life and the next childbirth, which are societal norms that meant women are expected to suffer alone and not complain. 50 As shown in tables 5 and 6, the episiotomy practice at different hospital levels showed difference. Compared with secondary hospitals, the rate of episiotomy in tertiary hospitals was lower, and the knowledge level of obstetricians and midwives was higher, probably as a result of staff qualification being higher and standardised training being disseminated with the latest evidence-based medicine in tertiary hospitals.…”
Section: Obstacles To Reducing the Rate Of Episiotomymentioning
confidence: 95%
“…Pain can cause reduced mobility and discomfort, interfere with the establishment of breastfeeding, newborn care development, and self-care activities, such as sleep, rest, urination, and bowel movements. It can also impact the sexual relationship and home life, causing psychological and emotional problems during the puerperium (1)(2) . Therefore, proper perineal pain management is necessary, including evidence-based best practices, for women's quality care in the postpartum period.…”
Section: Introductionmentioning
confidence: 99%